ANALISIS HUBUNG SINGKAT PARALEL EMPAT TRAFO IBT 500/150 KV 500 MVA GITET KEDIRI - ABDY CAHYA, MUHAMMAD WAHYU; Rizal, Royb F; Yumono, Fajar (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH, 2021)
Extra High Voltage Substation (GITET) Kediri is an electrical substation that serves 500, 150, and 20 kV systems. GITET Kediri in 2015 has three Inter Bus Transformers (IBT) 500/150 kV with each capacity of 500 MVA, then in 2020 there an addition of the same IBT. But, the 150 kV side has been configured since 2017. According to the IEC 60076-1 standard table 1.6 about parallel operation of the transformer, four IBTs are still eligible because the difference in impedance values ​​is ±7.5% (3.3%, 13.16%, 14.452%, and 14.375%). Breaking capacity of circuit breaker IBT 1,2,4 - 150 kVs, Kertosono, Jayakertas, Tulungagung 1&2, Banaran 1&2, Transformer 1, Coupler 1&2, Section A&B are 40 kA and for IBT 3 - 150 kV & Transformer 2 are 50 kA. Simulation and calculation current of parallel short circuit of four IBT for three phases are 26.978 and 26.548 kA, phase to ground are 29.659 and 30.097 kA, phase to phase are 23.363 and 23.066 kA, phase-phase to ground are 28.374 and 28.924 kA (phase AB) & 28,788 and 28,996 kA (phase BC). Based on that analysis, four IBTs can be parallel because it meets the difference in impedance and all of the 150 kV circuit breaker is feasible to operate because the fault current is smaller than the circuit breaker capacity